Leksyka związana z przygotowaniem piwa w poznańskich inwentarzach mieszczańskich z lat 1528-1601 - Müller, Aneta (Slavia Occidentalis, 2023)
The article aims to show Poznań bourgeois inventories as a source for studying lexis related to beer production. The excerpted vocabulary has been classified into lexical-semantic fields by means of textual and lexical meanings derived from the Dictionary of Polish Language of the 16th century. The possibility of supplementing the dictionary resources by lexical material obtained from the inventories has also been indicated – these are new meanings and numerous new attestations, especially relevant for lexemes recorded in the dictionary several times. The analysis was supplemented by a commentary on the origin of the lexica.